Distributed construction of data cubes from tuple stream. (1st January 2011) - Shimada, Teppei; Tsuchida, Takayuki; Tsuji, Tatsuo; Higuchi, Ken
We propose a distributed construction scheme of MOLAP data cubes in the related sites on a network. Using the implementation scheme of multidimensional datasets based on the history-offset tuple encoding method, the tuple stream can be processed efficiently to construct cuboids in real-time on each site, while MOLAP operations can be processed against one of the data cube versions in background. In this paper, we describe our tuple stream processing scheme and distributed data cube construction, then evaluate the required communication cost.